2021
DOI: 10.1007/s00595-021-02374-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of preoperative red-cell volume distribution width as a prognostic marker in patients undergoing radical surgery for pancreatic cancer

Abstract: Background and purpose A new noninvasive biomarker is being sought to predict the prognosis of patients with pancreatic cancer. Red-cell volume distribution width (RDW), a descriptive parameter for erythrocyte variation, has been shown to have prognostic value for some tumor types. Our purpose was to assess the RDW value to predict the prognosis of patients with pancreatic cancer. Methods The subjects of this retrospective study were 792 patients who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Many researchers have investigated the role of inflammation and inflammatory markers/indices in predicting the postoperative prognosis of various tumors, including PC (1,5,8). The ability of platelets to protect cancer cells from the immune response and facilitate their attachment to the endothelium and the antitumor role of lymphocytes support the hypothesis that PLR may be valuable in predicting prognosis in cancer patients (10,15). The mechanism underlying the prognostic value of PLR in PC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many researchers have investigated the role of inflammation and inflammatory markers/indices in predicting the postoperative prognosis of various tumors, including PC (1,5,8). The ability of platelets to protect cancer cells from the immune response and facilitate their attachment to the endothelium and the antitumor role of lymphocytes support the hypothesis that PLR may be valuable in predicting prognosis in cancer patients (10,15). The mechanism underlying the prognostic value of PLR in PC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is well established that inflammatory activation plays a key role in carcinogenesis and the tumor microenvironment (8). Despite the fact that information is limited regarding the mechanisms of these relationships (5), a number of inflammation markers and indices, including neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and lymphocytemonocyte ratio (LMR), and red cell distribution width (RDW), have been investigated for their potential importance in PC prognosis and diagnosis (9,10). Many authors have identified pretreatment RDW (10), NLR (11) and PLR (12) values as being associated with OS in patients with PC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prognostic value of inflammatory factors such as C-reactive protein, neutrophil to lymphocyte ratio (NLR), and red blood cell distribution width (RDW) has been assessed in various types of cancer. RDW, which reflects the variability of red blood cell size, has been reported to be associated with a worse prognosis in a variety of cancers, including pancreatic [ 11 ], colorectal [ 12 ], and breast cancers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%